Archetypes of common village pasture problems in the South Caucasus: insights from comparative case studies in Georgia and Azerbaijan - Regina Neudert (Resilience Alliance, 2019)
Complex social-ecological systems (SES), especially systems with common pool resources, often exhibit system dynamics characterized by emergence, where system properties cannot be fully explained by input variables. This causes challenges when it comes to explaining resource use problems because problem dynamics can differ from case to case despite similar input variables. Archetype analysis with its focus on identifying building blocks of nature-society relations might provide a means to tackle emergence and complexity in the analysis of resource use problems in SES. Using data from inter- and transdisciplinary research investigating comparative case studies on common village pasture management in the Caucasus region, we use the archetype approach with a focus on system archetypes that place particular emphasis on recognizing recurrent structures and internal dynamics. We apply three system archetypes, the Tragedy of the Commons, Shifting the Burden, and Success to the Successful, to different aspects of interlinked management problems that occur repeatedly in the case study data. Using SES variables characterizing the cases, we discuss variable combinations that may trigger specific dynamics. Moreover, we explore interlinkages between archetypical problems and discuss possible solutions based on self-governance. We find that the archetype approach with a focus on system archetypes resulted in consistent explanations of problem dynamics leading to important additional insights into root causes and internal archetypical dynamics compared with existing knowledge. Regarding problem solutions and policy recommendations, we show that viewing archetypical problems as interlinked in their actual case-study context leads to different recommendations than when each archetype is viewed on its own.